Marigolds (Tagetes spp.) for Nematode Management - R. Krueger; K. E. Dover; Robert McSorley; K. H. Wang (EDIS)
ENY-056, an 8-page fact sheet by R. Krueger, K. E. Dover, R. McSorley, and K. -H. Wang, introduces homeowners to the problem of root-knot nematodes, the use of marigolds as an allelopathic cover crop for nematode suppression. It describes the mode of action, planting tips, considerations, and frequently asked questions. Includes references and tables showing susceptibility of marigold varieties to root-knot and plant-parasitic nematodes in Florida. Published by the UF Department of Entomology and Nematology, August 2007.